Enhancement of thermal shock and slag corrosion resistance of MgO–ZrO2 ceramics by doping CeO2. Issue 10 (15th May 2022) - Jin, Endong; Yuan, Lei; Yu, Jingkun; Ding, Donghai; Xiao, Guoqing
Abstract: The purpose of this paper was to develop ceramics materials with high thermal shock resistance and corrosion resistance for preparing gas blowing components. In this paper, MgO-rich MgO–ZrO2 ceramics were obtained by using MgO powder and ZrO2 powder as starting materials and CeO2 as an additive. Changes in the properties in terms of thermal shock resistance, mechanical properties, and slag corrosion-resistance with chemical compositions were examined correlated to microstructure and phase changes. Especially, the effect of doping CeO2 on phase transition of zirconia in MgO-rich system was discussed. The results showed that doping amount of CeO2 significantly improved properties of MgO–ZrO2 ceramics. Especially when doping amount of CeO2 was 2 wt%, residual strength ratio was enhanced over 100% after thermal shock testing. In samples doped with CeO2, ZrO2 was stable in cubic or tetragonal form due to complete solution of CeO2, which was important reason for the improvement of various properties of MgO–ZrO2 ceramics.